Oxidative balance score and menopausal status: insights from epidemiological analysis and machine learning models - Dong, Chunlin; Ma, Ding; Yu, Jinjin; Gu, Ke; Lin, Yaying; Song, Jing; Wang, Yuan; Zhou, Yanjun (Frontiers in Nutrition, 2025)
BackgroundUnhealthy lifestyle habits, such as smoking, can impact oxidative stress. During oxidative stress, unnaturalized free radicals can damage DNA, proteins, and lipids, leading to cellular damage and death. A comprehensive measurement of various pro-oxidative and antioxidative exposures can reflect an individual's oxidative stress burden. However, studies on assessing the association between dietary and lifestyle factors related to oxidative stress and menopause were previously lacking.Materials and methodsA cohort of 2,813 women aged 40–60 years from the National Health and Nutrition Examination Survey conducted between 2003 and 2020 was identified as meeting the eligibility criteria. The associations of oxidative balance score (OBS) with the menopausal status were examined via weighted logistic regression models, and the odds ratios (ORs) of menopause onset were calculated with 95% confidence intervals (CIs). Machine learning models were developed and compared to classify the menopausal status based on the OBS and other epidemiological factors, with the interpretability of the models explored using the Shapley Additive Explanations method.ResultsFollowing adjustment for various confounding factors, OBS was reversely associated with menopause (OR: 0.97, 95% CI: 0.94–0.99, p = 0.010). When the OBS was categorized into quartiles, the association with menopause was still significant (p for trend = 0.009). The association of the OBS with menopause remained significant after excluding any each survey year cycles (p for trend < 0.050). The menopause classification models developed using TabFPN, Random Forest, CatBoost, and XGBoost achieved an area under the curve of 0.880, 0.884, 0.886, and 0.878, respectively. Based on the results from epidemiological analysis and machine learning models, the intake of magnesium, zinc, niacin, and vitamin B6 showed a decline in the early postmenopausal period and contributed in the model performance.ConclusionsOBS were reversely associated with the menopausal status, and the OBS might serve as an indicator of an individual's oxidative stress status for lifestyle interventions during the menopausal transition.